Ionic conductivity of chitosan membranes and application for electrochemical devices - Khiar, A.S.A.; Arof, Abdul Kariem; Winie, T.; Majid, Siti Rohana (John Wiley & Sons, 2006)
Lithium (Li+)- and proton (H+)-conducting chitosan-based electrolytes have been prepared using the solution cast technique. The experimental results obtained using chitosan as the host polymer are compared with those of other Li+- and H+-complexes. The Rice and Roth model was used to explain the variations in the conductivity observed. The exponent, n, in Joncsher's universal power law equation sigma(omega) = sigma(dc) + A'omega(n) was analyzed as a function of temperature for the chitosan sample containing 41 vol% H3PO4. The analysis suggests that the conduction mechanism follows that proposed by the overlapping large polaron tunneling model. The chitosan membranes can be used as electrolytes in solid state batteries, electric double layer capacitors and fuel cells. However, there is still scope for improvement. Copyright (c) 2006 John Wiley & Sons, Ltd.